Effects of dynamical masses of gluons and quarks on hadronic B decays - Zanetti, C. M.; Natale, A. A. [UNESP] (AIP Publishing, 2010)
We study hadronic annihilation decays of B mesons within the perturbative QCD at collinear approximation. The regulation of endpoint divergences is performed with the help of an infrared finite gluon propagator characterized by a non-perturbative dynamical gluon mass. The divergences at twist-3 are regulated by a dynamical quark mass. Our results fit quite well the existent data of B 0→D s-K + and B 0→ D s-*K + for the expected range of dynamical gluon masses. We also make predictions for the rare decays B 0→K -K +, B s0→π -π +, π 0π 0, B +→D s(*) +K̄ 0, B 0→D s±(*)K ± and B s0 →D±(*) π ±, D 0π 0. © 2010 American Institute of Physics.
Keywords: B meson; hadronic decays; infrared cutoff